2001
DOI: 10.1007/s003450100221
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 1 inhibition in the treatment of lower urinary tract dysfunction: From bench to bedside

Abstract: Anticholinergic drugs are currently the therapy of choice to treat urgency and urge incontinence. However, muscarinergic receptor blockers with adequate selectivity for detrusor smooth muscle are not available. Also, in contrast to the normal detrusor, the unstable detrusor neurotransmission seems to be at least partially regulated by non-cholinergic (NANC) pathways. These factors may explain the common side effects and the limited clinical efficacy of these compounds. Specific modulation of intracellular seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 12 publications
1
52
0
Order By: Relevance
“…90 Studies with the PDE 1 inhibitor vinpocetin, which reduces the breakdown of cAMP, showed relaxant effects in vitro but poor clinical efficacy in OAB/DO patients. 132 PDE 4, which also preferably hydrolyses cAMP, has been implicated in the control of bladder smooth muscle tone. PDE 4 inhibitors reduced the in vitro contractile responses of guinea pig, 133 suppressed rhythmic bladder contractions of the isolated guinea pig bladder, 5 and also suppressed non-voiding contractions in rats with bladder outlet obstruction.…”
Section: Phosphodiesterase (Pde) Inhibitorsmentioning
confidence: 99%
“…90 Studies with the PDE 1 inhibitor vinpocetin, which reduces the breakdown of cAMP, showed relaxant effects in vitro but poor clinical efficacy in OAB/DO patients. 132 PDE 4, which also preferably hydrolyses cAMP, has been implicated in the control of bladder smooth muscle tone. PDE 4 inhibitors reduced the in vitro contractile responses of guinea pig, 133 suppressed rhythmic bladder contractions of the isolated guinea pig bladder, 5 and also suppressed non-voiding contractions in rats with bladder outlet obstruction.…”
Section: Phosphodiesterase (Pde) Inhibitorsmentioning
confidence: 99%
“…Five isoforms of PDEs (1)(2)(3)(4)(5) were isolated and demonstrated in human and porcine detrusor in functional studies. [16,17] The effect of vardenafil on cyclic nucleotide levels and bladder contraction was investigated in rat detrusor by Werkstrom et al [18] Relexation was accompanied with increased levels of both cAMP and cGMP, and it was proposed that vardenafil-induced relaxation of rat detrusor was mediated by cAMP through inhibition of cGMP dependent cAMP-PDE. Relaxation of bladder neck was achieved with high levels of sildenafil in contracted human bladder neck by phenylephrine which suggests that PDE inhibitors may have potential effect to relax the bladder outlet.…”
Section: Discussionmentioning
confidence: 99%
“…The central role of cyclic AMP and cyclic GMP and PDE isoenzymes in the control of various tissue functions has been established and the pharmacological concept of increasing tissue levels of cyclic nucleotides, for example, by the use of selective PDE inhibitors, to treat diseases of the urogenital tract, such as urinary stone disease (ureterolithiasis), urinary Cyclic GMP binding proteins in the human clitoris S Ückert et al incontinence, symptoms of the so-called benign prostatic syndrome including lower urinary tract symptoms and bladder outlet obstruction, has been evaluated in clinical studies. [18][19][20] Based on the hypothesis that the response to sexual stimulation in women is, in part, mediated by the same biological pathways than in the male, it has been speculated as to whether the application of PDE inhibitors may also facilitate female genital smooth muscle relaxation, thus resulting in an improvement of subnormal arousal. 21 A few efforts were made in order to characterize PDE isoenzymes of the human clitoris; however, these studies were mainly limited to the cyclic GMP-specific PDE5, whereas other cyclic GMP- Cyclic GMP binding proteins in the human clitoris S Ückert et al binding PDE isoenzymes, such as PDE2, PDE3, PDE9, PDE10 or PDE11, or other key proteins of the NO/cyclic GMP pathway, such as cGK, have either not or only randomly been investigated.…”
Section: Discussionmentioning
confidence: 99%